Forma????o continuada de professores no ??mbito da inclus??o: diversidade e adversidades - Takase, Daniele Gonzalez Agnani (2011)
The purpose of the present study is to investigate the relationship between the inclusion of pupils with special educational needs into the regular system of education and the teachers??? continuous professional training. The research question is to investigate the need for continuous professional training of teachers of the first four grades of the Primary Education of the Council for Education of the State of S??o Paulo which include pupils with special educational needs in their classrooms. The analysis of the need for continuous professional training is extremely important to understand the different problems that inclusion involves. To perceive the teachers??? concerns, their experiences, their difficulties and their expectations with regard to continuous professional training as well as their position toward inclusion contributes to a greater reflection which permits changes and the pursuit of the improvement of the quality of teaching. This study is based upon the hypothesis which states that teachers??? participation in continuous professional training promotes inclusive education. The group under research was composed of 26 teachers of the four first grades of Primary Education of the Council for Education of S??o Paulo which include or have already included pupils with special educational needs in their classrooms. The teachers??? report was guided by the qualitative approach of research; as methodical tools they used the questionnaire, the bibliographical research and documental sources. The analysis of the categories ???Continuous Professional Training??? and ???Inclusive Education??? was based upon Ant??nio N??voa???s and Maria Teresa Egl??r Mantoan???s theoretical referentials and on other authors who studied this subject matter, thus contributing to a greater deepening of the study. The results allow us to affirm that the inclusion of pupils with special educational needs into regular education implies changes in the attitude and in the pedagogical practice, in the organization of schools, in the curricula and, particularly, in the implementation of proposals of continuous professional training to teachers.